Tyrosine‐derived polycarbonate nerve guidance tubes elicit proregenerative extracellular matrix deposition when used to bridge segmental nerve defects in swine. Issue 7 (12th October 2020) - Burrell, Justin C.; Bhatnagar, Divya; Brown, Dan P.; Murthy, N. Sanjeeva; Dutton, John; Browne, Kevin D.; Laimo, Franco A.; Ali, Zarina S.; Rosen, Joseph M.; Kaplan, Hilton M.; Kohn, Joachim; Cullen, D. Kacy
Abstract: Promising biomaterials should be tested in appropriate large animal models that recapitulate human inflammatory and regenerative responses. Previous studies have shown tyrosine‐derived polycarbonates (TyrPC) are versatile biomaterials with a wide range of applications across multiple disciplines. The library of TyrPC has been well studied and consists of thousands of polymer compositions with tunable mechanical characteristics and degradation and resorption rates that are useful for nerve guidance tubes (NGTs). NGTs made of different TyrPCs have been used in segmental nerve defect models in small animals. The current study is an extension of this work and evaluates NGTs made using two different TyrPC compositions in a 1 cm porcine peripheral nerve repair model. We first evaluated a nondegradable TyrPC formulation, demonstrating proof‐of‐concept chronic regenerative efficacy up to 6 months with similar nerve/muscle electrophysiology and morphometry to the autograft repair control. Next, we characterized the acute regenerative response using a degradable TyrPC formulation. After 2 weeks in vivo, TyrPC NGT promoted greater deposition of pro‐regenerative extracellular matrix (ECM) constituents (in particular collagen I, collagen III, collagen IV, laminin, and fibronectin) compared to commercially available collagen‐based NGTs. This corresponded with dense Schwann cell infiltration and axon extension across the lumen. These findings confirmed results reported previously in a mouse model and reveal that TyrPC NGTs were well tolerated in swine and facilitated host axon regeneration and Schwann cell infiltration in the acute phase across segmental defects ‐ likely by eliciting a favorable neurotrophic ECM milieu. This regenerative response ultimately can contribute to functional recovery.